BOOK REVIEW: GRACE UPON GRACE. REFLECTIONS ON THE MEANING OF LIFE - M. Laubscher (Acta Theologica)
Cilliers, J. (Stellenbosch: African Sun Media, 2020) 96 pp. ISBN: 978-1-928314-71-4 (R230); e-ISBN: 978-1-928314-72-1 (R185). DOI: https://doi.org./10.18820/9781928480617  is reviewed by M. Laubscher.